Increased Amygdala and Insula Activation During Emotion Processing in Anxiety-Prone Subjects. - Stein, Murray B.; Simmons, Alan N.; Feinstein, Justin S.; Paulus, Martin P. (American Journal of Psychiatry, 2007)
Objective: Increased amygdala reactivity during processing of certain types of emotional stimuli (e.g., fear, anger) has been observed in patients with anxiety disorders such as social phobia and posttraumatic stress disorder (PTSD). It is uncertain whether this heightened amygdala reactivity is specific to treatment-seeking patients with anxiety disorders or is a general feature of individuals with increased anxiety-related temperamental traits. Method: Thirty-two physically healthy subjects 18-21 years old were recruited from a large pool of college students. Of these, 16 were chosen on the basis of scoring in the upper-15th percentile on a measure of trait anxiety (anxiety-prone group), and 16 were chosen on the basis of scoring in the normative range (40th-60th percentile). Subjects participated in functional magnetic resonance imaging (fMRI) during an emotion face assessment task that has been shown to reliably engage amygdala and associated limbic structures. Results: Anxiety-prone subjects had significantly greater bilateral amygdala and insula activation to emotional faces than did the anxiety-normative comparison subjects. Higher scores on several measures assessing anxiety proneness (e.g., neuroticism, trait anxiety, and anxiety sensitivity) were associated with greater activation of the amygdala (predominantly left-sided) and the anterior insula (bilateral). Conclusions: Increased amygdala and insula reactivity to certain types of emotional processing is seen in young adults with increased anxiety-related temperamental traits. Therefore, this brain emotion-processing profile may be a functional endophenotype for proneness to (certain kinds of) anxiety disorders. Reprinted by permission of the publisher.